Deep ice coring at Dome Fuji Station, Antarctica - Yoshiyuki Fujii; Nobuhiko Azuma; Yoichi Tanaka; Akiyoshi Takahashi; Kunio Shinbori; Yoshiki Nakayama; Hideaki Motoyama; Kazuo Katagiri; Shuji Fujita; Morihiro Miyahara; Takao Kameda; Takashi Saito; et al. (Antarctic Record, 1999)
Deep ice coring was carried out at Dome Fuji Station, Antarctica in 1995 and 1996 following a pilot borehole drilled and cased with FRP pipes in 1993,and reached 2503.52m in December 1996. Total numbers of ice coring runs below the pilot borehole and chip collection were 1369 and 837 respectively. The mean coring depths per run and per day were 1.75m and 8.21m respectively. We report the outline of the coring operation, the system, coring method, and troubles encountered during the coring work.